2010
DOI: 10.1161/circulationaha.109.935338
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Papillary Muscle Infarction Detected by Late Gadolinium-Enhanced Magnetic Resonance Imaging in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: Background-The frequency of papillary muscle infarction (PapMI) without rupture has not been fully investigated in vivo. Furthermore, the relationship between papillary muscle dysfunction and mitral regurgitation (MR) has been controversial in patients with ST-segment elevation myocardial infarction. Therefore, the aim of this study was to assess the frequency and clinical characteristics of PapMI without rupture using late gadolinium-enhanced magnetic resonance imaging (MRI) in patients with ST-segment elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 35 publications
5
45
3
4
Order By: Relevance
“…Patients with partial PM infarction did not differ from patients with MI other than a lack of PM involvement regarding ischemic mitral regurgitation. Compared to results published by Tanimoto et al [17] reporting a prevalence of 40 %, PM infarction was observed less frequently in the present study with a prevalence of 23 %. These results are more in line with a frequency of 19 -32 % as published in autopsy studies [18].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Patients with partial PM infarction did not differ from patients with MI other than a lack of PM involvement regarding ischemic mitral regurgitation. Compared to results published by Tanimoto et al [17] reporting a prevalence of 40 %, PM infarction was observed less frequently in the present study with a prevalence of 23 %. These results are more in line with a frequency of 19 -32 % as published in autopsy studies [18].…”
Section: Discussioncontrasting
confidence: 93%
“…Published data indicate that PM infarction is usually the result of ischemia of the inferior and inferolateral left ventricular myocardium [17,26]. Due to the vascular anatomy of the PM, the anterior PM is much less frequently affected [11,27].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In the vast majority (90%), rupture involves the posteromedial papillary muscle, presumably a consequence of its single source blood supply from either the RCA or LCX coronary artery. 7 In contrast, the anterolateral papillary muscle has a dual source blood supply emanating from both the LAD and LCX coronary arteries, thus providing protection from ischemic rupture. 7 For the patient described herein, an unfortunate constellation of coronary artery occlusions interrupted this dual source blood supply and provided the anatomic substrate for infarction and subsequent rupture.…”
Section: N Discussionmentioning
confidence: 99%
“…7 In contrast, the anterolateral papillary muscle has a dual source blood supply emanating from both the LAD and LCX coronary arteries, thus providing protection from ischemic rupture. 7 For the patient described herein, an unfortunate constellation of coronary artery occlusions interrupted this dual source blood supply and provided the anatomic substrate for infarction and subsequent rupture.…”
Section: N Discussionmentioning
confidence: 99%
“…[4,5] In a recent study by Tanimoto et al, [5] the prevalence and clinical significance of papillary muscle infarction was detected via gadolinium-enhanced magnetic resonance imaging in patients with MI. In this study composed of 47 patients with papillary muscle infarction, the posterior papillary muscle was involved in (77%) while the anterior papillary muscle was involved in only (23%).…”
Section: Discussionmentioning
confidence: 99%